Cytochrome P450 whole cell biohydroxylation of alkanes - Seeger, Danielle (Department of Chemical Engineering, 2025)
Production of higher-value fine chemicals via bio-based catalytic alkane activation are becoming increasingly relevant in the context of sustainability. Linear alkanes, sourced from fossil fuel reserves and as by-products in gas-to-liquid technology and CO2-to-power strategies, both through Fischer Tropsch activities, can serve not only as a low-cost fuel or solvent, but also as a precursor to produce valuable long chain alcohols. Effective use, or resource efficiency, with respect to alkanes is important in sustainable processing. Alkanes contain unreactive hydrocarbon bonds and cracking processes apply high temperatures and pressures to split these inert molecules into smaller and reactive molecules. Although widely applied, cracking suffers from poor selectivity and is resource heavy and environmentally burdening. Biocatalysis has shown potential for highly regio-selective alkane oxidation under mild conditions. Enzyme catalytic mechanisms evolved to catabolise fatty molecules in an organism’s metabolic pathway. Biocatalysis harnesses these evolved pathways to produce value added chemicals. Cytochrome P450 (CYP) monooxygenases such as CYP153A6 have previously shown excellent 95% selectivity for hydroxylation at the terminal carbon on n-octane and CYP153A13 has shown promising activity on n-octane and n-decane. In the present study, whole cell biocatalysts were prepared by expressing CYPs in E. coli BL21(DE3) and suspended in aqueous media required to maintain whole cell health. Alkanes applied were immiscible with the aqueous phase, resulting in a ‘2-Liquid Phase System’ (2LPS). Alkane accessibility to the enzyme in the whole cells significantly constrains scalability of biocatalysis due to transfer across the aqueous-organic interface and the cellular membrane to reach CYPs. The extent to which alkanes are transferred is determined by variables such as solubility, thermodynamic equilibrium, cell membrane permeability, temperature etc. The kinetics of the biocatalytic reaction are partly dependent on physicochemical variables, but also on biological parameters such as cellular health, enzyme expression etc. It was shown that although CYP153A13 showed superior coupling efficiencies compared to multicomponent enzyme systems, fusion proteins suffer from low expression levels and cytoplasmic proteolytic truncation, lowering its concentration and activity compared to CYP153A6. High Cell Density Cultures (HCDCs) were used to circumvent CYP153A13’s low expression. HCDCs of both CYP153A6 and CYP153A13 resulted in larger 1-octanol volumetric production rates by 10- and four-fold respectively compared to the LCDC counterparts. The turnover number of CYP153A6 and -A13 LCDCs, however, were respectively 2- and 7- fold higher than their HCDC counterparts, illustrating the oxygen and nutrient limitation of HCDCs. The multicomponent CYP153A6 system was expressed with high functionality and showed descending activity with: n-octane > n-decane > n-nonane, caused by a combination of alkane solubility and transmembrane transport. Although n-decane is less soluble in water than n-nonane, the ‘odd-even’ effect of alkanes resulted in high in vivo activity on n-decane. UNIF-LL predictions illustrated that BEHP reduces the amount of alkane in the aqueous phase than in the absence of BEHP. Therefore, it was illustrated that BEHP regulates the amount of substrate in the aqueous phase, which decreases the toxicity of the alkane substrates towards the whole cells. Therefore, while substrate solubility plays a role in availability to the whole cell biocatalyst which would impact the rate of biocatalytic reaction, cellular health maintenance is also important. This proved that factors related to aqueous substrate solubility play a larger role in the outcomes of 2LPS whole cell biocatalytic reaction kinetics as well as factors such as cellular health. The study showed that although substrate solubility plays an important role in biocatalytic performance, substrate solubility could not be used as the sole indicator of predicting biocatalytic performance and factors such as enzyme expression, membrane transport, enzyme-substrate affinity and physical substrate properties should be considered. To investigate the enzyme-substrate affinity, apparent Michaelis Menten (MM) constants (𝐾𝑚 𝑐 ) of each enzyme-substrate pair were determined from experimental data, of product concentration, accumulated over time using least squares nonlinear regression. 𝐾𝑚 𝑐 constants, however, represented both enzyme-substrate (ES) and substrate-solvent interactions. To determine the true affinity of each ES pair without the interference of substrate-solvent interactions on ES interactions, thermodynamic activity-based constants (𝐾𝑚 𝑎 ) were determined. This approach paves the way for the future development of ‘one-pot’ biocatalytic systems containing multiple different enzymes and substrates. A process flowsheet using the UNIF-LL model was developed and a theoretical calculation were used to determine activity coefficients, which were in turn used to determine the 𝐾𝑚 𝑎 constants. The 𝐾𝑚 𝑐 constants of CYP153A6 illustrated a 17-fold and two-fold larger affinity for n decane and n-nonane compared to n-octane, respectively. By excluding the effects of substrate-solvent interactions, CYP153A6 had an affinity twice as large for n-nonane compared to both n-octane and n decane. Therefore, while the 𝐾𝑚 𝑐 constants depicted that n-decane had the highest affinity with CYP153A6, this resulted from unfavourable molecular interactions between n-decane and the aqueous solvent, rather than favourable ES affinity. The 𝐾𝑚 𝑐 constants suggested that n-decane is the preferred substrate of CYP153A13 by two-fold compared to n-octane, but 𝐾𝑚 𝑎 values revealed that CYP153A13 had a six-fold larger affinity for n-octane than n-decane. The UNIF-LL model predicted substrate available in the aqueous phase at phase equilibrium for each alkane in the 2LPS. These predicted aqueous phase substrate concentrations were compared to the enzyme concentration and the MM constants, respectively. From these comparisons, it was determined that the reactions catalysed by CYP153A6 on n-octane and n-nonane were not limited by substrate concentration, whilst the reactions catalysed by CYP153A13 on n-decane were limited by substrate concentration. These results, together with enzyme expression characterisation mentioned earlier, means that CYP153A6 processes can be improved using enzyme engineering techniques, whilst CYP153A13 processes can be improved using enzyme engineering to improve enzyme expression levels as well as substrate delivery enhancement techniques. These findings highlighted the impact of substrate solubility on substrate partitioning into the aqueous phase to be available to the biocatalyst. However, once the substrate reaches the aqueous phase, effective bioconversion relies on adequate transmembrane transport, sufficient enzyme expression levels, ES affinity, and the effectiveness of the reaction mechanism. Therefore, both physiochemical and biological factors play a role in the demand-based delivery system. This demand-based delivery system is governed by the rate of substrate transfer across the liquid-liquid and membrane barriers, as well as the amount of substrate converted into product by the catalytic mechanism of the enzyme, thereby allowing more substrate to partition into the aqueous phase. Overall, the approach developed could be used to enhance the kinetic studies of CYP153 whole cell alkane primary hydroxylation in two-liquid-phase-systems, a field that receives little attention but shows importance in the goal of scaling up such systems. Globally, researchers and industry share interest in the biohydroxylation of linear chain alkanes due to their high-end properties and value, but poor solubility limits techno-economic feasibility and large-scale application. This study showed promising compatibility of CYP enzymes with medium chain alkanes (C8 C9 C10), but showed the challenges presented in molecular biology such as enzyme expression. Moreover, substrate solubility of linear alkanes impacts the location of the reaction within a 2LPS, accessibility and the apparent ES affinity. Overall, the study developed an integrated approach to investigate the reaction kinetics of an alkane whole cell hydroxylation 2LPS by considering the limitations arising from both molecular biology and biochemistry as well as thermodynamics. From this, the interdisciplinarity of biocatalysis was enhanced by integrating aspects of molecular biology and biochemistry into the greater context of chemical engineering. The findings can be used to facilitate research in alkane bio-activation process control, optimisation and scaling up by implementing the use of multiple enzymes and substrates simultaneously.